FINANCIAL PERFORMANCE ANALYSIS AND EVALUATION OF PALM OIL AGROINDUSTRY: AN INDONESIA EXPERIENCE - Wiwiek Mardawiyah Daryanto (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
Indonesia is the world largest producer and exporter of crude palm oil (CPO). The export of CPO has increased by 46% from 15.1 million ton in 2008 became 27 million ton in2016. However, the value of the export decreased by 11.67%, from US$ 21.1 billions in2014 to US$ 18.64 billions in 2015. This was caused by the decrease of CPO export pricesignificantly (33.33%), from US$ 1,033/ton in 2008 to US$ 689/ ton in 2016. The DecreeNo.KEP-100/MBU/2002 issued by Indonesia Ministry of State-Owned Enterprises (SOEs)on June 2002 provides the mandatory of measuring and rating the financial healthcondition of SOEs. This study aims to analyze and evaluate the financial health conditionof three Palm Oil SOEs under Indonesia Ministry of Agriculture: (1) PT PerkebunanNusantara I; (2) PT. Perkebunan Nusantara III; (3) PT. Perkebunan Nusantara IV forperiodsof 2011 – 2015. The results of investigating of eight financial ratios: return onequity, return on investment, cash ratio, currentratio, collectionperiod, inventoryturnover,totalassetturnover, totalequity to totalasset, then be validated by the decree of the SOEsministry to conclude the financial health condition of the companies. The result shows thatthe three Palm Oil SOEs have achieved financial health condition levels with rank ratingsas follows: (1) PT. Perkebunan Nusantara IV (AA,AA,A,AA,BBB), (2) PT PerkebunanNusantara III (A,AA,A,BBB,BBB), and (3) PT Perkebunan Nusantara I(A,A,A,BB,CCC).